2021
DOI: 10.37939/jrmc.v25i2.1600
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of surgical site infection on the surgical floor; Increasing resistance to routine antibiotics

Abstract: Objective: To know the spectrum of surgical site infections in general surgical patients so that specific strategies can be developed to decrease the morbidity caused by these infections.Material and Methods: All the patients who underwent general surgical operations on an emergency basis at the surgical unit of the District headquarters teaching hospital Rawalpindi from 01-01-2016 to 31-12-2017 were evaluated for surgical site infections. Surgical site infections suspected clinically were confirmed by culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…31 The SSI incidence rate in the thyroidectomy was reported by 10.9% in Nawabsha city. 32 Due to post-surgical complications, the mortality rate was up to 10.6% in Karachi. The Khyber Pakhtunkhwa province hospitals reported SSIs rate from 5.78% to 9.2%.…”
Section: Discussionmentioning
confidence: 99%
“…31 The SSI incidence rate in the thyroidectomy was reported by 10.9% in Nawabsha city. 32 Due to post-surgical complications, the mortality rate was up to 10.6% in Karachi. The Khyber Pakhtunkhwa province hospitals reported SSIs rate from 5.78% to 9.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate sterilization measures especially at remote public sector hospitals and antibiotic resistance has caused rise in SSI. 11,12 Various studies are published before in which microbiology and drug sensitivity from swabs of SSI are tested. The aim of this systematic review is to gather recent information about microbiology and sensitivity of various antibiotics against the microorganisms isolated in cultures.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…However other factors may be involved as wellThe growing incidence and emergence of Methicillin resistance staph aureus (MRSA) in wounds of SSI is alarming and on the rise. Study conducted by Iqbal M et al12 in Rawalpindi showed 5% of all staph aureus positive cultures were MRSA while 1 % were vancomycin resistant staph aureus (VRSA). This growing incidence is alarming.…”
mentioning
confidence: 99%